2015
DOI: 10.4338/aci-2014-12-ra-0113
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Nursing Homes for the Future of Health Information Exchange

Abstract: SummaryObjective: Our purpose was to describe how we prepared 16 nursing homes (NHs) for health information exchange (HIE) implementation. Background: NH HIE connecting internal and external stakeholders are in their infancy. U.S. initiatives are demonstrating HIE use to increase access and securely exchange personal health information to improve patient outcomes. Method: To achieve our objectives we conducted readiness assessments, performed 32 hours of clinical observation and developed 6 use cases, and cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“… 7 , 20 , 26 , 27 , 34 - 37 In multiple studies, staff also reported a need for greater IT support, ideally on-site. 7 , 9 , 18 , 25 - 27 , 38 Several studies described help lines that were not available after hours and had slow response times. 9 , 24 , 25 , 27 Two reported that on-site and intensive IT support available 24/7 were instrumental to HIT implementation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 20 , 26 , 27 , 34 - 37 In multiple studies, staff also reported a need for greater IT support, ideally on-site. 7 , 9 , 18 , 25 - 27 , 38 Several studies described help lines that were not available after hours and had slow response times. 9 , 24 , 25 , 27 Two reported that on-site and intensive IT support available 24/7 were instrumental to HIT implementation.…”
Section: Resultsmentioning
confidence: 99%
“… 42 When examined by direct observation, staff had fewer in-person or verbal interactions after HIT implementation but used a greater variety of communication methods. 29 , 30 , 38 , 43 , 46 Other studies found that staff expressed a continued preference for verbal communication on issues deemed important. 30 , 43 , 46…”
Section: Resultsmentioning
confidence: 99%
“…Our literature search narrowed 210 results down to 22 by assessing each for suitability to our research objective. 2 3 4 5 6 7 8 9 18 19 20 21 22 23 24 25 26 27 28 29 30 We excluded 16 results because they were outside our target date range of 2010 to 2017. Another 157 results were excluded when we used the filters of English-only, full-text, and academic journals.…”
Section: Resultsmentioning
confidence: 99%
“…This was consistent with a previous study mentioning that barriers to facility and management support may impede the successful enactment of electronic documentation. 31,32 Minimum leadership can mean that potential motivational aspects in embracing changes are overlooked. 33 Leadership and the roles of the leaders in closely evaluating and monitoring staff attitudes and adaptation throughout the implementation of a system are pertinent during the transition trajectory.…”
Section: Discussionmentioning
confidence: 99%